Peningkatan kompetensi digital marketing womenpreuneur di Desa Babatan Kecamatan Kadugede Kabupaten Kuningan - Rina Masruroh; Yasir Maulana; Muhammad Musyfiq Muflih (IKIP SILIWANGI, 2024)
Babatan Village is one of the villages located in Kadugede District, Kuningan Regency, the majority of the population's livelihood is as Micro, Small and Medium Enterprises (MSMEs). Micro, Small and Medium Enterprises are part of community business units that play an important role in the recovery and strengthening of the community's economy. However, the majority of MSMEs in Babatan Village do not have adequate digital competence. Digital competence is very necessary in increasing the competitiveness of MSMEs and increasing the market reach of MSMEs. Apart from that, the majority of MSME actors in Babatan Village are women, this is unique because various studies show that women always play an important role in the family economy. Therefore, this community service aims to increase the digital competence of female MSMEs or womenpreneurs in Babatan Village, Kadugede District. The methods used in this community service are observation, digital marketing workshops, evaluation in the form of pre-tests and post-tests and post-workshop mentoring. The result of this activity is an increase in the digital competence of womenpreneurs in Babatan Village, Kadugede District, Kuningan Regency